Character Education Values in Indonesian Proverbs - Firman Alamsyah Mansyur; Cecep Nuryadin; Muchtar Muchtar; Sahril Sahril; Wa Ode Aksa Amayliya (ELS Journal on Interdisciplinary Studies in Humanities, 2021)
Indonesian proverbs contain positive cultural values which are part of the character education of the Indonesian people. Therefore, this study aims to explain the values of character education in Indonesian proverbs. This research method is descriptive qualitative. Data were collected from Indonesian proverb books. Data analysis was carried out by identifying and classifying the proverbs based on the educational values they contain. This study finds that Indonesian proverbs have a minimum of 13 character education values: religious, honesty, discipline, justice, hard king, humility, independence, love of knowledge, loyalty, courage, frugal living, and social care. These values are very important for the younger generation. Therefore, the use and preservation of Indonesian proverbs in learning or the world of Indonesian education are very important to continue.